Interações topoclimáticas entre o urbano e o Parque Natural Municipal dos Morros, em Santa Maria/RS. - Silva, Aline Nunes da (2022)
This research aimed to investigate the atmospheric dynamics between the urban and natural environment of the municipality of Santa Maria, within a topoclimatic scale. For this, the nossa Senhora do Perpétuo Socorro neighborhood, located in the northern part of the urban area of Santa Maria, was defined as the study area. Inserted in the neighborhood is the first Integral Protection Conservation unit of Santa Maria, the Parque Natural Municipal dos Morros. The study area is relevant with regard to the preservation and conservation of local biodiversity, since it is located in a transition zone between the two biomes that occur in the territory of Rio Grande do Sul, the Atlantic Forest biome (remaining) and Pampa biome. In addition, the study area is also inserted in a transition area of morphosculptural units (Serra Geral, marked by the Edge of the Meridional Plateau, and the Peripheral Depression) which gives a great altimetric amplitude to the neighborhood. Within this topoclimatic context, the research aims to investigate the topoclimatic interactions between the urbanized area of the Nossa Senhora do Perpetuo Socorro neighborhood and the Parque Natural Municipal dos Morros (PNMM) Conservation Unit, in Santa Maria/RS. Five Local Climate Zones (LCZs) were identified in the study area. Also, the average, absolute maximum and minimum temperatures recorded in the study area were higher in the urban environment, as well as evapotranspiration. The PNMM presented an average air temperature higher than the PSO point during the month of July. The vertical thermal gradient of study area has a monthly variation from -0.99°C/100m to 0.15°C/100m. The accumulated volume of rainfall during the survey period was higher in the PNMM in relation to the PSO. Also, the records of thermal inversion and orographic effect in the study area were observed. The most active atmospheric systems in each phenomenon were the Polar Migratory Anticyclone, in the phase of decharacterization, and the passage of the polar front through the territory of Rio Grande do Sul, respectively. Finally, it is considered that the topoclimatic variability in the Nossa Senhora do Perpétuo Socorro neighborhood, as well as by the atmospheric processes that occur in the urban environment and that accentuate the heating and cooling of the atmospheric layer near the surface.